Peran Akuntansi Keperilakuan Dalam Peningkatan Kualitas Sustainability Reporting Pada Aspek Tata Kelola (Governance) Studi Kasus KOPA TTN Jember - Nadia Nur Rizkiana; Aisyah Salvira; Aminatus Zahriyah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of behavioral accounting in improving the quality of sustainability reporting on governance aspects at the Tarutama Nusantara Agribusiness Producers Cooperative (KOPA TTN) Jember. The study used a qualitative approach with a case study method to gain an in-depth understanding of individual behavior, organizational culture, and governance practices implemented within the cooperative. Data collection was conducted through in-depth interviews, observation, and documentation of cooperative administrators, administrative staff, and operational personnel involved in the organizational reporting process. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing. The results show that behavioral factors such as integrity, responsibility, professionalism, information transparency, and leadership commitment have a significant influence on the quality of sustainability reporting on governance aspects. The implementation of an internal control system, periodic evaluations, Standard Operating Procedures (SOPs), and a culture of transparency can improve the accountability and credibility of organizational reports. In addition, the implementation of sustainability standards such as the Sustainable Tobacco Program (STP) and the ISO quality management system also supports more structured and sustainable governance practices. This study also found that the main challenges in maintaining reporting quality stem from individual behavioral factors, such as late reporting and low work discipline. Therefore, strengthening behavioral control through leadership, training, and a reward and punishment system is a crucial strategy in supporting transparent, accountable, and sustainable sustainability reporting.